GAMBARAN KADAR SGOT,SGPT DAN BILIRUBIN PADA PASIEN KOLELITIASI DI RSI SITI RAHMAH PADA TAHUN 20121-2023 - Mhd Nurhuda; Yusti Siana; Mutiara Annisa (Nusantara Hasana Journal, 2024)
Cholelithiasis or gallstones form from an imbalance of chemical content in bile that causes the deposition of one or more of the bile components. According to data from the World Health Organization (WHO), the incidence of cholelithiasis in the world was 11.7% in 2017. Risk factors are closely related to cholelithiasis such as age, sex, and BMI. Usually, gallstones that block the bile ducts can cause damage to liver cells and inhibit bile flow which can affect liver function such as SGOT, SGPT, and bilirubin which will indicate liver damage. Objective: Knowing how the description of SGOT, SGPT, and bilirubin levels in cholelithiasis patients at RSI Siti Rahmah Padang in 2021-2023. Method: This type of research is a categorical descriptive study with a cross- sectional study approach design, with the estimated population in this study being patients with cholelithiasis at RSI Siti Rahmah Padang in 2021-2023 with 86 samples using purposive sampling techniques. Univariate data analysis is presented in the form of frequency. Results: From a total sample of 86 people, most of the cholelithiasis sufferers at the age of ≥ 51 years were 41 people (47.7%), most were female at 58 people (67.4%), most with normal BMI at 55 people, most with normal SGOT levels at 62 people (72.1%), most with normal SGOT levels at 53 people (61.6), Most with normal total bilirubin levels of 56 people (65.1%), most with elevated total bilirubin levels of 48 people (55.8%), most with normal indirect levels of 60 people (69.8%). Conclusion: Most patients with ≥ age 51 years, most patients are female, most patients with normal levels of SGOT, SGPT, total bilirubin and indirect bilirubin and most patients with elevated bilirubin levels.